2020
DOI: 10.1016/j.jgar.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Could Bordetella pertussis vaccine protect against coronavirus COVID-19?

Abstract: According to the World Health Organization (WHO), as of today, there are 2.165.500 confirmed cases of the novel coronavirus disease (COVID-19) and 145.705 deaths in over 185 countries. Unfortunately, despite the tremendous efforts to develop a vaccine initiated by various leading health institutions all over the world, it may be 18 months before a vaccine against the coronavirus is publicly available. We are proposing a theory about testing the use of the Bordetella pertussis vaccine to protect against COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The results reported here add to the literature reviewed in the Introduction that cast doubt on studies reporting that BCG, polio, or DPT vaccinations may protect against COVID-19 acquisition or death [64][65][66][67][68][69][70][71][72][73][74][75][76]. However, one important caveat must be mentioned, which is that it was not possible in this study to differentiate between nations using acellular pertussis vaccines, those using whole-cell pertussis vaccines, and those using both as part of their vaccination programs.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The results reported here add to the literature reviewed in the Introduction that cast doubt on studies reporting that BCG, polio, or DPT vaccinations may protect against COVID-19 acquisition or death [64][65][66][67][68][69][70][71][72][73][74][75][76]. However, one important caveat must be mentioned, which is that it was not possible in this study to differentiate between nations using acellular pertussis vaccines, those using whole-cell pertussis vaccines, and those using both as part of their vaccination programs.…”
Section: Discussionmentioning
confidence: 69%
“…Finally, diphtheria-tetanus-pertussis vaccination [ 74 , 75 , 76 , 77 ] and polio vaccination [ 78 ] have also been suggested as possible prophylactics against COVID-19, but at present, no ecological study exists to support these possibilities. Published studies have found no protective benefit [ 5 , 44 , 45 ], and antibody titers against tetanus do not correlate with COVID-19 protection [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 Several other vaccines may ready the immune response with partial specificity, and thereby produce similar protective effects. [10][11][12] Indeed, there appear to be protein sequence similarities of proteins in pathogens targeted by common vaccines and SARS-CoV-2, 13,14 with combination vaccines for the infectious diseases diphtheria, tetanus, and pertussis (DTP vaccine) containing cross-reactive epitopes with SARS-CoV-2. 15 Additionally, a team of computer scientists applied an artificial intelligence algorithm in an exploratory fashion to millions of biomedical publications, curated assay databases, and protein databanks.…”
mentioning
confidence: 99%
“…Other researchers propose a theory of testing the Bordetella pertussis vaccine for protection against COVID-19 in adults [ 31 ]. Others argue that whooping cough is a vaccine-preventable infectious disease of the airways and shares many similarities with COVID-19, including transmission mode and clinical features.…”
Section: Possible Correlation Between Vaccinations and Covid-19: Rmentioning
confidence: 99%